MMP-3 activation is involved in copper oxide nanoparticle-induced epithelial-mesenchymal transition in human lung epithelial cells. Issue 10 (26th November 2021) - Zhang, Yuanbao; Mo, Yiqun; Yuan, Jiali; Zhang, Yue; Mo, Luke; Zhang, Qunwei
Abstract: Copper oxide nanoparticles (Nano-CuO) are widely used in medical and industrial fields and our daily necessities. However, the biosafety assessment of Nano-CuO is far behind their rapid development. Here, we investigated the adverse effects of Nano-CuO on normal human bronchial epithelial BEAS-2B cells, especially determined whether Nano-CuO exposure would cause dysregulation of MMP-3, an important mediator in pulmonary fibrosis, and its potential role in epithelial-mesenchymal transition (EMT). Our results showed that exposure to Nano-CuO, but not Nano-TiO2, caused increased ROS generation, MAPKs activation, and MMP-3 upregulation. Nano-CuO-induced ROS generation was not observed in mitochondrial DNA-depleted BEAS-2B ρ 0 cells, indicating that mitochondria may be the main source of Nano-CuO-induced ROS generation. Pretreatment of the cells with ROS scavengers or inhibitors or depleting mitochondrial DNA significantly attenuated Nano-CuO-induced MAPKs activation and MMP-3 upregulation, and pretreatment of cells with MAPKs inhibitors abolished Nano-CuO-induced MMP-3 upregulation, suggesting Nano-CuO-induced MMP-3 upregulation is through Nano-CuO-induced ROS generation and MAPKs activation. In addition, exposure of the cells to Nano-CuO for 48 h resulted in decreased E-cadherin expression and increased expression of vimentin, α-SMA, and fibronectin, which was ameliorated by MMP-3 siRNA transfection, suggesting an important role of MMP-3 in Nano-CuO-induced EMT. Taken together, our study demonstrated that Nano-CuO exposure caused mitochondrial ROS generation, MAPKs activation, and MMP-3 upregulation. Nano-CuO exposure also caused cells to undergo EMT, which was through Nano-CuO-induced dysregulation of ROS/MAPKs/MMP-3 pathway. Our findings will provide further understanding of the potential mechanisms involved in metal nanoparticle-induced various toxic effects including EMT and pulmonary fibrosis.